Local food-based education: Utilization of moringa leaves (Moringa oleifera, l.) for stunting prevention - Amelia, Renny; Suharyani, Ine; Rizikiyan, Yayan; Lestari, Trisna; Sulastri, Lela; Supriyadi, Yadi; Azzahra, Siti; Ningsih, Widia; Mutmainah, Iin; Maryam, Diana Dwi; Shadrina, Ghesani Nur; Yasmin, Yasmin; Nurhidayah, Sri; Adiibah, Siti (Community Empowerment, 2025)
Stunting, a condition of impaired growth in children due to chronic malnutrition, is a significant public health problem. This community service aimed to increase the knowledge of the community, particularly pregnant women, regarding the potential of Moringa oleifera leaves as a healthy snack alternative in stunting prevention. This activity employed a pre-test post-test design with an intervention of counseling and training on making chicken nuggets fortified with Moringa oleifera leaves. The target participants were pregnant women with low upper arm circumference and mothers with stunted children. Evaluation of participants' understanding of stunting and the benefits of Moringa oleifera leaves was conducted before and after the intervention. The evaluation results showed an increase in participants' understanding of stunting and the benefits of Moringa oleifera leaves, as indicated by an increase in the average score of correct answers in the post-test compared to the pre-test. A hedonic test on the chicken nuggets fortified with Moringa oleifera leaves showed a very high level of liking for taste and color, and a high level of liking for aroma and appearance. The texture of the nuggets was identified as an aspect requiring further improvement.